Ultrahigh density nucleation leading to extraordinary long-cycle dendrite-free Li metal deposition. (15th October 2021) - Cao, Tianci; Cheng, Xiaopeng; Wu, Rui; Wang, Mingming; Niu, Jiajia; Liu, Huan; Liu, Xianqiang; Lu, Junxia; Zhang, Yuefei
Abstract: Li metal is the prospective candidate of next generation anode materials. However, the growth of dendritic Li during electrochemical cycling has severely hindered the practical application of rechargeable Li-metal batteries. Herein, "seaweed" graphene paper (SGP) is designed for 3D matrix of Li metal anode to address the growth of dendrites. SGP has abundantly exposed edges of graphene sheets and realizes ultrahigh density nucleation. Compared with nonuniform lithium deposition on parallelly stacked GP which has been observed by in-situ scanning electron microscopy, electrochemical deposition behavior of Li in SGP manifests as uniformly distributed granular lithium. Significant decrease of nucleation barrier can be observed during the dendrite-free deposition. With the elimination of dendritic Li growth and excellent stability of SGP host, the lithium anode based on SGP can run over 2500 cycles without short circuit and exhibits low voltage hysteresis. When matched with cathode LiCoO2, the full battery also presents stable cycling. There is no trace of lithium dendrite even after 1200 cycles which proves continuously regulating effect on lithium dendrites by SGP host. This work further develops potential application of graphene materials in the Li anode with high reversibility for stable cycling Li metal batteries. Graphical abstract: Ultrahigh density nucleation is realized by changing the stacked manner of graphene sheets. Compared with parallelly stacked graphene paper (GP), "seaweed" stacked GP (SGP) has more exposed edges which can supply abundant nucleation sites. As the host, SGP eliminates the growth of dendritic Li during cycling and assembled Li@SGP symmetrical batteries can stably plating/stripping for over 2500 cycles at 1.0 mA cm −2 . Image 1 Highlights: Nonuniform lithium deposition on parallelly stacked GP was observed by in-situ SEM. Ultrahigh density nucleation realized by "seaweed" GP with abundant exposed edges leads to dendrite-free deposition. Corresponding batteries present extraordinary long-cycle dendrite-free performance.